Na dnie oka. Dziesiąta Muza z perspektywy stulecia - Hendrykowski, Marek (Przestrzenie Teorii, 2022)
The article attempts to reread Karol Irzykowski’s classic treatise on cinema and to recognize the importance of its significance in the context of the entirety of changes and achievements of humanistic culture in the interwar period.